Asymptotic behavior of entire functions of improved regular growth in the metric of L^p[0, 2π] - Khats’, R.V. (Carpathian Mathematical Publications, 2013)
We describe an asymptotic behavior of entire functions of improved regular growth with zeros on a finite system of rays in the metric of L^p[0, 2π].